2014
DOI: 10.1007/s00701-014-2259-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of diffusion-weighted MRI for tumor consistency and resection rate of nonfunctional pituitary macroadenomas

Abstract: DW MRI was useful to predict the tumor consistency, collagen content and the chance of removal of pituitary macroadenomas through endoscopic transsphenoidal surgery, and is recommended in the preoperative patient evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 19 publications
2
36
0
Order By: Relevance
“…Pierallini et al found that fibrous tissue and high cellularity with a low nucleus‐to‐cytoplasm ratio can produce a decrease in the SI, whereas an increase in free water may cause a large increase in the SI on T 2 WI. These results indicate that multiple factors, including fibrous content, cellularity, nuclear‐to‐cytoplasmic ratio, and amount of free water in the extracellular space, may influence the SI of the tumor on T 2 WI, which may therefore limit the diagnostic utility of T 2 WI in the assessment of consistency of macroadenomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pierallini et al found that fibrous tissue and high cellularity with a low nucleus‐to‐cytoplasm ratio can produce a decrease in the SI, whereas an increase in free water may cause a large increase in the SI on T 2 WI. These results indicate that multiple factors, including fibrous content, cellularity, nuclear‐to‐cytoplasmic ratio, and amount of free water in the extracellular space, may influence the SI of the tumor on T 2 WI, which may therefore limit the diagnostic utility of T 2 WI in the assessment of consistency of macroadenomas.…”
Section: Discussionmentioning
confidence: 99%
“…PITUITARY TUMORS originating from adenohypophysial cells are the most common lesions of the sella turcica, which are believed to comprise 10–15% of all primary brain tumors . The endoscopic transsphenoidal technique has been applied as a preferred minimally invasive surgical approach to remove pituitary macroadenomas .…”
mentioning
confidence: 99%
“…These systems create maps from preoperative magnetic resonance imaging (MRI) and computed tomography (CT) imaging and allow the real-time tracking of surgical instruments’ position during surgery, thereby allowing the surgeon to see what lies beyond the view of the endoscope. Together, the endoscope and navigation platform allow the surgeon better visualization of tumor boundaries 24,31 , tumor composition 1,36 , and the tumor’s relationship to nearby cranial nerves and branches of the ICA 21 . Injury to these neural and vascular structures leads to significant patient morbidity, and possibly mortality 16 .…”
Section: Introductionmentioning
confidence: 99%
“…They found no correlation between the appearance of macroadenomas and T2W MRI appearance. Several of the above studies have concluded the same [6,14,15]. …”
Section: Discussionmentioning
confidence: 68%
“…Alimohamadi et al [14] found that an ADC value of 0.600-0.740 × 10-3 mm2/s was associated with more residual tumor after transsphenoidal resection. However, ADC values were not predictive of surgical consistency.…”
Section: Discussionmentioning
confidence: 99%